Can primary care data be used to evaluate the effectiveness of tobacco control policies?: data quality, method development and assessment of the impact of smokefree legislation using data from the Health Improvement Network - Szatkowski, Lisa Catherine (2011)
Background: Smokefree legislation is just one of a number of tobacco control policies introduced in the UK in the last decade in an attempt to curb the harm caused by smoking. Whilst such legislation is known to have reduced non-smokers’ exposure to environmental tobacco smoke, less is known about whether the introduction of a smoking ban encourages existing smokers to attempt to quit and to seek support to do so from appropriate sources such as their general practitioner. High quality data are needed to evaluate the effectiveness of legislation in prompting smokers to change their smoking behaviour, and data collected routinely in primary care may provide such an opportunity. However, there is little contemporary evidence about the quality of the smoking data recorded in primary care, nor how best to analyse these data, which must be addressed before the resource can be used to evaluate the effectiveness of tobacco control policies.